Pengaruh Edukasi dengan Media Poster terhadap Kepatuham Minum Tablet Tambah Darah Pada Remaja di Wilayah Kerja Puskesmas Darul Azhar - Isni Renuati; Hairiana Kusvitasari; Lisda Handayani; Desilestia Dwi Salmarini (Journal of Innovative and Creativity, 2025)
Background: According to the BKKBN, only 0.9% of the 76.2% adolescents who receive TTD that was regularly drink the TTD. The percentage of adolescent in South Borneo at 2022 who took TTD was 42,03% while in Tanah Bumbu Regency was 89.3%. This prevalence will decrease in 2023 by 12.44%. Darul Azhar Public Health Center's achievement for adolescent girls' compliance drinking TTD is quite low, only 12.44%. The school with the lowest adherence to drinking TTD was MA Darul Azhar, where was only 9 of 98 adolescents (9.18%). Health education can be done through various media. One of media that can be used is poster. The advantages of using poster are easy to make, has a wide target, attractive, and easy to place everywhere. Objective: To determine the effect of education using poster media on compliance to drinking TTD among adolescents at Darul Azhar Public Health Center. Method: This research method uses pre-experimental research: one group pretest-posttest without control group. This research was conducted on 56 teenage girls at MA Darul Azhar with total sampling and analyzed using the Wilcoxon test. Instrument of this research is questionnaire. Results: Pretest results showed that 92.9% of respondents did not comply an 7.1% complied. Meanwhile, in the posttest, 55.4% complied and 44.6% did not comply. Test results Wilcoxon shows p value 0.000 < α 0.05. Conclusion: Education using poster media has an influence on adolescents' compliance to consuming TTD at MA Darul Azhar